2021
DOI: 10.1111/opn.12403
|View full text |Cite
|
Sign up to set email alerts
|

Feeling valued versus abandoned: Voices of persons who have completed a cognitive assessment

Abstract: Aim: To describe older persons' experiences of a cognitive assessment and possible neuropsychiatric symptoms [NPS] related to a neurocognitive diagnosis. Background: A cognitive assessment in primary care is offered to persons with suspected dementia with subsequent referral to a specialist clinic if required. The assessment process, with the likelihood of receiving a dementia diagnosis, is surrounded by uncertainty with long waiting times. Although NPS are common among persons with cognitive impairment person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…A key consideration was the impact that a diagnosis of poor memory can have upon stroke survivors and how this could have a detrimental impact on mood and rehabilitation engagement This finding is mirrored in a study of those undergoing post stroke dementia screening [40] . Likewise, in a Swedish population participant concern about abandonment post testing with an ‘abnormal’ test result emerged [41] .…”
Section: Discussionmentioning
confidence: 99%
“…A key consideration was the impact that a diagnosis of poor memory can have upon stroke survivors and how this could have a detrimental impact on mood and rehabilitation engagement This finding is mirrored in a study of those undergoing post stroke dementia screening [40] . Likewise, in a Swedish population participant concern about abandonment post testing with an ‘abnormal’ test result emerged [41] .…”
Section: Discussionmentioning
confidence: 99%
“…The present study is associated with two previous studies describing the experiences of 23 persons at the start and end of their medical assessment of cognitive impairment ( Tyrrell et al, 2021a ; Tyrrell et al., 2021b ). The patients’ family members, who accompanied them to the clinic, were also interviewed on both occasions concerning their experiences of supporting the person with cognitive impairment and of the assessment process.…”
Section: Methodsmentioning
confidence: 98%
“…Family members often describe struggling to navigate the care system ( Prorok et al, 2017 ). The assessment process can be lengthy and stressful for both the persons with cognitive impairment and the care partners ( Prorok et al, 2017 ; Tyrrell et al, 2021a ). In the conversation which discloses a dementia diagnosis, it is critical that the person and their family members are given sufficient information and are not deprived of hope ( Poyser & Tickle, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients reported that they did not understand the process of a cognitive assessment or the possible outcomes, they had concerns about living with a neurocognitive disorder, and reported feelings of shock and violation following the assessment. 21 …”
Section: Introductionmentioning
confidence: 99%